Seminal characterization of some elite Ethiopian indigenous breeds of bull - SORI, HUNDERRA; PRASAD, SHIV; ZEWDIE, EMIRU (The Indian Journal of Animal Reproduction, 2023)
The semen of six indigenous bulls consisting of Barca, Boran, Horro and Sheko breeds maintained at National Artificial Insemination Center (NAIC), Kaliti, Addis Ababa, (Ethiopia) were evaluated for physico-morphological parameters, biochemical parameters (GOT, GPT, ACP, ALP, total protein) and hormonal assay (testosterone). Semen was collected for thirteen weeks, once a week by using artificial vagina. The overall mean (SE) value for the semen characteristics studied were volume 4.84 (0.20) ruJ, mass motility 3.15 (0.11 ), individual motility 68.72 (1.37) %, concentration 1.54 (0.07) billions/ml, total count 7.35 (0.4 7) billions/ejaculate, viable number 5.10 (0.33) billions/ejaculate, total morphologically normal number 7.12 (0.45) billions/ejaculate, live percentage 79. 73 (0.65), percent morphologic normal 94.70 (0.38), per cent normal acrosome 96.99 (0.60), GOT I 530.91 (60. I 5) u/1, GPT 131.99 (9.36) U/L, ALP 3333.98 (608.84) U/L, ACP 8003.68 (716.06) U/L, total protein 7.38 (0.26) gm/di, testosterone 2.84 (0.3) ng /ml. It could be concluded that seminal attributes were comparable to normal fertile bulls of other breeds based on the evaluation of fresh semen parameters.